Australian liberals and the moral middle class : from Alfred Deakin to John Howard - Brett, Judith, 1949- (Cambridge University Press, 2003)
This book, by award-winning author Judith Brett, provides the very first complete history of the Australian liberal tradition, and then of the Liberal Party from the second half of the twentieth century.